Brazil - Progressive Low-Income Housing : Alternatives for the Poor - World Bank (Washington, DC, 2013)
This report aims to analyze key aspects of the low-income housing sector in Brazil, and to provide an analytical framework for reviewing alternatives to addressing the lack of adequate formal housing and urban services for the poor. It addresses four fundamental questions for policymakers in the housing sector in Brazil: First, should the government be involved in policy interventions in the low-income segment of the housing market? Second, if policy action is appropriate, what roles should policymakers at the federal, state, and municipal levels play? Third, should the government's key interventions in the market be focused on the supply, or demand side of the market? Finally, how can the government structure a comprehensive policy to deal with the failure of the housing market to provide adequate shelter for the poor? The report begins with a brief outline of the nature, and extent of the low-income housing problem, describes the policies in place to address the lack of housing, suggests a methodological framework for assessing the paucity of low-income housing in light of international experiences, and identifies the main building blocks of a strategy for low-income housing in Brazil. There are four main reasons why a considerable backlog in housing persists: (a) low-income levels; (b) high supply costs; (c) market failures; and (d) distortions in public policy. Considering low-income housing directions, we need to refer to: Access to Land; Access to Finance; Appropriate Standards; Basic Infrastructure Provision; Targeted Subsidies; and, Inclusion and Partnership. Ensuring that the above elements are incorporated in future low-income housing initiatives requires important new directions necessary to further facilitate an enabling approach. Reforms are advocated in the areas of policy, institutions, and regulations; moving away from limited, project-based approaches, adopting the enabling principle. This new approach may not have a monopoly on wisdom, nor does it have all the answers needed for the complex, difficult problem of housing the urban poor, but it does provide the most promising way forward if the problem is to be addressed at a scale commensurate with its magnitude, and adequate to improve substantially the housing conditions of the poor.